2003
DOI: 10.1093/humrep/deg492
|View full text |Cite
|
Sign up to set email alerts
|

Preconception sex selection for non-medical reasons: a representative survey from the UK

Abstract: BACKGROUND: Preconception sex selection for non-medical reasons raises serious moral, legal and social issues. The main concern is based on the assumption that a freely available service for sex selection will distort the natural sex ratio and lead to a severe gender imbalance. However, for a severe gender imbalance to happen, at least two conditions have to be met. First, there must be a signi®cant preference for children of a particular sex, and second, there must be a considerable demand for preconception s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Among the UK citizens of Pakistani origin, 78% wished to have a family with an equal number of boys and girls, 10% preferred only boys and 12% preferred more boys than girls. In other words, none of the Pakistani respondents desired to have more girls than boys, leave alone, only girls (Dahl et al, 2003b).…”
Section: Discussionmentioning
confidence: 98%
“…Among the UK citizens of Pakistani origin, 78% wished to have a family with an equal number of boys and girls, 10% preferred only boys and 12% preferred more boys than girls. In other words, none of the Pakistani respondents desired to have more girls than boys, leave alone, only girls (Dahl et al, 2003b).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, we end with pointing out that the phenomena we have demonstrated still is fairly marginal, which we are able to detect with such precision merely because of the magnitude of our data and with apparent preferences for a child of a specific sex being much weaker than the desire for having a child of each sex. There are no signs that gender preferences for children in the Nordic countries are so strong that they have produced more drastic outcomes like sex-selective abortion (for related evidence from Germany and the U.S., see Dahl et al 2003;: a closer examination of our data (not shown) reveals that there is no tendency at all of any changes in the sex composition of children born by different demographic sub-groups, neither in Sweden nor in Finland.…”
Section: Discussionmentioning
confidence: 66%
“…Attention for this topic has also been growing rapidly in recent studies on advanced western societies (e.g., Diekmann & Schmidheiny 2004;Hank & Kohler 2000;Lundberg 2005;Marleau & Saucier 2002;Raley & Bianchi 2006). This development might, first, be due to medical advances that facilitate parents' deliberate choice of their child's sex (e.g., Dahl et al 2003Dahl et al , 2006. Secondly, it has been argued that in modern low-fertility societies the influence of the sex composition of previous children on couples' childbearing behavior might intensify, because factors affecting the decision to have another child should become more important (e.g., Gray & Evans 2005;Sloane & Lee 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they are premised on contentious assumptions about the existence of a heterogeneous cultural mass in industrialized northern hemisphere countries. First, there is evidence of 'son preference' in European countries and the USA, although to a lesser extent than in some South and East Asian countries (Hank and Kohler, 2000;Dahl et al, 2003aDahl et al, ,b, 2006van Balen, 2006). Second, there are many diaspora communities living in industrialized northern-hemisphere countries, some from cultures in which sex selection has been found to result in demographic imbalance.…”
Section: Harm Is Caused By Sex Selectionmentioning
confidence: 99%